Tampiog Dance Tradition as a Source of Inspiration for Painting Works - Yana, I Wayan Wirta; Kondra, I Wayan; Budiarta, I Dewa Putu Gede (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
The Tampiog Dance tradition literally means kicking fire in its implementation involving the youths, undagi and stakeholders as participants and witnessed directly by village krama around the village of Manukaya Let. This shows that the Tampiog organizational culture that is formed in a system called Pekraman village is able to move each other to make the implementation of its activities successful. The Tampiog Dance Tradition (Kicking Fire) is a mythology that has been accepted as an inheritance by the people of Manukaya Let Village for generations. This tradition sounds and looks unique and rare, simply not found anywhere else. After carrying out a joint prayer at the Balai Agung Temple or the Village Temple, the village. So in the evening the Tampiog Dance tradition was immediately carried out. This tradition was carried out by the Pemangku who started this ceremony and was continued by the Banjar youth Manukaya Let. In carrying out this tradition, all residents were expected to be able to think cleanly, speak the truth and do what was noble. In this independent project, the author displays a tradition that stands out in the Tampiog tradition that is highlighted, namely the tradition of kicking a fire.